2018
DOI: 10.1021/acs.est.8b03535
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from Natural Gas Production Sites in the United States: Data Synthesis and National Estimate

Abstract: We used site-level methane (CH4) emissions data from over 1000 natural gas (NG) production sites in eight basins, including 92 new site-level CH4 measurements in the Uinta, northeastern Marcellus, and Denver-Julesburg basins, to investigate CH4 emissions characteristics and develop a new national CH4 emission estimate for the NG production sector. The distribution of site-level emissions is highly skewed, with the top 5% of sites accounting for 50% of cumulative emissions. High emitting sites are predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(149 citation statements)
references
References 33 publications
15
134
0
Order By: Relevance
“…Our data suggests that emission volumes are not proportional to production, and therefore regulations to limit methane emissions must consider both low-and high-producing wells. These findings reflect recent observations elsewhere-Omara et al also found that site-level proportional loss rate from low producing sites is higher than at high producing sites [34]. Future studies with larger sample sizes could help to establish the contribution of methane emissions from low producing wells.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our data suggests that emission volumes are not proportional to production, and therefore regulations to limit methane emissions must consider both low-and high-producing wells. These findings reflect recent observations elsewhere-Omara et al also found that site-level proportional loss rate from low producing sites is higher than at high producing sites [34]. Future studies with larger sample sizes could help to establish the contribution of methane emissions from low producing wells.…”
Section: Resultssupporting
confidence: 90%
“…The mean emission rate from tank sources is 52 kg CH 4 /d (95% C.I. [34,89]), almost an order of magnitude larger than the overall mean emission rate across all components. The outsized role of tanks in contributing to overall methane emissions at natural gas facilities has been a defining feature in many recent studies, and points to a critical need for tank-focused LDAR regulations [31].…”
Section: Resultsmentioning
confidence: 97%
“…Accurate quantification of emissions is necessary if the most cost‐effective reduction strategies are to be targeted, but quantification of emission flux in plumes remains an imprecise art. Kang et al () showed the disproportionate impact of major gasfield leaks—the so‐called “superemitters.” In the United States Omara et al () found the top 5% of sites accounted for 50% of cumulative emissions. Identifying, quantifying, and stopping these superleaks is the first step in emission reduction.…”
Section: Methodsmentioning
confidence: 99%
“…Kang et al (2016) showed the disproportionate impact of major gasfield leaks-the so-called "superemitters." In the United States Omara et al (2018) found the top 5% of sites accounted for 50% of cumulative emissions. Identifying, quantifying, and stopping these superleaks is the first step in emission reduction.…”
Section: General Methodologymentioning
confidence: 99%
“…The low end of our range accounts for regional variability in the CH 4 content of natural gas across production basins through a production-weighted national average [34]. However, other possible drivers of regional variability may not be captured, including local production levels, device operating practices and malfunctions, as well as regulations [16,35]. For the high end of our range we therefore rely on a higher, regional top-down estimate from [5], with an understanding that this is not a national estimate but allows the estimated range to span both high and low observations in the literature, and recognizes that the national average rate is a subject of ongoing debate.…”
Section: Estimating Baseline Power Sector Ch 4 Emissionsmentioning
confidence: 99%